2019
DOI: 10.1038/s41598-019-52040-9
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-1 Modulates Rho/ROCK-Mediated Membrane Morphology and Calcium-Dependent Intracellular Chloride Flux

Abstract: Membrane morphology is an important structural determinant as it reflects cellular functions. The pentaspan membrane protein Prominin-1 (Prom1/CD133) is known to be localised to protrusions and plays a pivotal role in migration and the determination of cellular morphology; however, the underlying mechanism of its action have been elusive. Here, we performed molecular characterisation of Prom1, focussing primarily on its effects on cell morphology. Overexpression of Prom1 in RPE-1 cells triggers multiple, long,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…Collectively, the data suggest that prominin-1 plays a role in modulating cellular architecture by regulating the expression of cholesterol metabolism-related genes, shifting the physiological condition from a naïve state to a regenerative state, which leads to enhanced axon regeneration after injury. A recent report by Hori and colleagues ( 84 ) showed that Prom1 overexpression induced cell membrane extensions at the rear edge of the moving RPE1 cells, a human immortalized retinal pigmented epithelium-derived cell line. The induced fibers are rich in cholesterol, seemingly in conflict with our observation that Prom1 overexpression leads to down-regulation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the data suggest that prominin-1 plays a role in modulating cellular architecture by regulating the expression of cholesterol metabolism-related genes, shifting the physiological condition from a naïve state to a regenerative state, which leads to enhanced axon regeneration after injury. A recent report by Hori and colleagues ( 84 ) showed that Prom1 overexpression induced cell membrane extensions at the rear edge of the moving RPE1 cells, a human immortalized retinal pigmented epithelium-derived cell line. The induced fibers are rich in cholesterol, seemingly in conflict with our observation that Prom1 overexpression leads to down-regulation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that the expression of Edn2 and Bcl3 in the Prom1 -KO retina was induced by light stimulation, the mechanism underlying this effect remains unclear. Nevertheless, our study suggests the possibility that an imbalance in intracellular ions caused by the loss of Prom1 (given that Prom1 regulates chloride conductance activated by intracellular calcium uptake [12]) may impair the function of cytoplasmic organelles such as mitochondria and the endoplasmic reticulum, and thereby elicit a stress response. Studies to identify the transcriptional regulatory elements of Edn2 and the corresponding transcription factors and upstream signalling pathways underlying its photoactivation are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Prom1 has been detected in cilia, which are protrusive structures at the cell membrane and key signalling hubs [10], and to be essential for maximisation of Hedgehog signalling in neural stem cells [11]. We recently showed that Prom1 activates the small GTPase Rho and regulates chloride conductance triggered by intracellular calcium uptake [12].…”
Section: Introductionmentioning
confidence: 99%
“…Ttyh2 has also been shown to be involved in the formation of cell membrane extensions as Hori et al ( 2019 ) found that overexpressing ttyh2 in retinal pigment epithelium cells caused an increase in membrane extensions in those cells.…”
Section: Physiological Functions Of Tweety Proteinsmentioning
confidence: 99%